Improving Learning Outcomes of Electrical Lighting Installation with Project-Based Learning at SMKN 3 Tondano - Lembong, Jemmy; Tatali, Yosua (Jurnal Edunitro, 2023)
This study aims to determine whether there are differences in learning outcomes of psychomotor abilities in designing and installing Electrical Lighting Installations implementing a project-based learning methodology with students using traditional learning models in class XI TITL SMK Negeri 3 Tondano. This study used an experimental method, with a sample of 15 students of XI TITL 1 as the experimental class and 15 students of XI TITL 2 as the control class. Data analysis was carried out by t-test and requirements test, namely normality test using Lilieforce test and the Levene test. The results showed a difference between the learning outcomes of designing and installing electrical lighting installations for groups of students implementing a project-based learning methodology with students using traditional learning models. The average psychomotor ability learning outcomes of students who use project-based learning models are higher than those of conventional learning models. Based on this statement, it can be concluded that there is an effect of project-based learning models to improve students' psychomotor learning outcomes in the material of designing and installing Electrical Lighting Installations in class XI students of SMK Negeri 3 Tondano.